Preparation method of side chain Schiff base type liquid crystal epoxy resin

By introducing side chain Schiff alkaline liquid crystal elements into epoxy resin, changing the molecular chain structure and making them arranged in a regular and orderly manner along a certain direction, the problem of low thermal conductivity of traditional epoxy resins is solved, significantly improving thermal conductivity, while retaining insulation and flame retardant properties.

CN119707876APending Publication Date: 2025-03-28HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411510718.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The low thermal conductivity of traditional epoxy resins limits their application in the field of microelectronics, and filling with high thermal conductivity fillers will reduce dielectric strength and insulation resistance, affecting mechanical properties and processing costs.

Method used

By introducing side chain Schiff alkaline liquid crystal motifs into epoxy resin, the molecular chain structure is changed, and they are arranged in a regular and orderly manner in a certain direction, improving crystallinity or building a local microscopic orderly structure, thereby improving thermal conductivity.

Benefits of technology

The thermal conductivity of epoxy resin is significantly improved, and the thermal conductivity coefficient is increased from 0.188W/(m·K) to 0.434W/(m·K), while retaining good insulation and flame retardant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707876A_ABST
    Figure CN119707876A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of side chain Schiff base type liquid crystal epoxy resin, and relates to a preparation method of epoxy resin. The structural orderliness of a liquid crystal cross-linked network is regulated and controlled on the basis of molecular structure design, methylene arylamine groups with good liquid crystal characteristics exist in the molecular structure of the provided Schiff base type liquid crystal epoxy monomer, and a liquid crystal structure is introduced to a molecular chain through an intrinsic synthesis way; in the curing process, a compact cross-linked network structure can be formed, and the acting force between molecules can be enhanced, so that the heat-conducting property of the side-chain Schiff base type liquid crystal epoxy resin is greatly improved. The test result shows that the liquid crystal interval is 138-170 DEG C, and the liquid crystal epoxy resin monomer is nematic phase liquid crystal. The liquid crystal epoxy resin composite material prepared from the side chain Schiff base type liquid crystal epoxy resin provided by the invention has excellent heat conductivity, and the heat conductivity is 0.434 W / mK, which is obviously improved compared with the heat conductivity of 0.188 W / mK of common E-51 epoxy resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing epoxy resin. Background Art

[0002] As equipment and electronic devices develop towards high integration and miniaturization, the heat generated per unit volume of equipment increases dramatically. The resulting temperature rise will accelerate the aging and failure of insulating dielectrics, greatly reducing the reliability and life of electrical and electronic equipment. Therefore, heat dissipation has become a bottleneck problem for high power density equipment and devices. Epoxy resin (EP), as one of the most important thermosetting polymers, has excellent mechanical properties, thermal stability, corrosion resistance and electrical insulation properties, as well as low cost and excellent processability. It is widely used in adhesives, electronic packaging, mechanical engineering, aerospace, military defense and other fields, and occupies about 70% of the thermosetting resin market. However, due to its own random cross-linking structure, the thermal conductivity of traditional epoxy is very low, only 0.16~0.20W / (m·K), which is 1 to 3 orders of magnitude lower than that of ceramic and metal materials, limiting its application in the field of microelectronics. In order to improve the thermal conductivity of epoxy, many studies have adopted the use of high thermal conductivity fillers. However, when the content of thermally conductive particles is too high, while the thermal conductivity is improved, the dielectric strength and insulation resistance are also significantly reduced, which will change the electric field concentration inside the epoxy and distort the electric field. The introduction of too many filler particles will inevitably deteriorate its mechanical properties, and will also bring new challenges in terms of cost and processing. Under this premise, the present invention only adjusts the structure of epoxy molecules so that they are arranged regularly and orderly along a certain direction, improves their crystallinity or constructs a local microscopic ordered structure, so as to improve the thermal conductivity of the cyclic resin. In polymers, liquid crystal polymers have a rigid liquid crystal unit structure, which will increase the mean free path of phonons and greatly improve the thermal conductivity of polymers. Therefore, a Schiff base structure liquid crystal unit with an imine characteristic group is grafted onto an epoxy monomer to improve its thermal conductivity, i.e., a Schiff base type liquid crystal epoxy resin. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for preparing a side chain Schiff base type liquid crystal epoxy resin.

[0004] A method for preparing a side chain Schiff base type liquid crystal epoxy resin is specifically completed by the following steps:

[0005] 1. Preparation of P1:

[0006] ①, 4-biphenyl formaldehyde, p-aminophenol and anhydrous ethanol are mixed to obtain a mixed solution I;

[0007] ②, dissolve p-toluenesulfonic acid in anhydrous ethanol to obtain mixed solution II;

[0008] ③. Add the mixed solution II dropwise to the mixed solution I to obtain a mixed solution III; reflux the mixed solution III for a period of time to obtain a yellow precipitate; wash the yellow precipitate, and then dry it to obtain an intermediate product P1;

[0009] 2. Dissolve the intermediate product P1 and epichlorohydrin in isopropanol, then add tetrabutylammonium bromide, and then heat under reflux for a period of time under stirring and a temperature of 85°C to 95°C, dropwise add a 30% by mass NaOH solution, and continue to stir and react at 85°C to 95°C for a period of time to obtain a reaction product; wash and dry the reaction product to obtain a side chain Schiff base type liquid crystal epoxy resin.

[0010] Principle of the present invention:

[0011] The invention mainly changes the molecular chain structure through an intrinsic liquid crystal modification method, and synthesizes an epoxy resin with an imine group from the perspective of molecular structure design. The imine group is a typical Schiff base structure and has good and stable liquid crystal properties. A liquid crystal epoxy resin composite material is prepared with ordinary E-51 epoxy resin under the action of a curing agent, methyl hexahydrophthalic anhydride. Since the liquid crystal material has a regularly arranged lattice and a unique liquid crystal domain, a highly ordered cross-linked network is formed through the curing process. Under the premise of ensuring that the insulation performance is not reduced, a heat conduction path is constructed, and the thermal conductivity of the epoxy resin is improved by reducing phonon scattering.

[0012] Advantages of the present invention:

[0013] The invention proposes a side chain liquid crystal epoxy resin monomer with an imine Schiff base structure, which has good and stable liquid crystal properties, and its internal lattice arrangement is regular and highly ordered, and it is easier to form a crystal structure; the liquid crystal epoxy resin monomer has an ordered crystal structure, so that it can form a special cross-linking structure with E-51 epoxy resin during the curing process, and retains the regularly arranged lattice and the liquid crystal domain unique to the liquid crystal material, and the microstructure is anisotropic and the macrostructure is isotropic, and at the same time, the thermal conductive structural defects of the E-51 epoxy resin are improved, and a thermal conductive path is constructed for phonons The highly ordered local structure effectively reduces the scattering of phonons, increases the mean free path of phonons, reduces thermal resistance, and improves the thermal conductivity of the composite material; at the same time, the liquid crystal epoxy resin composite material containing imine groups also has good flame retardant properties; according to the records of the embodiments, the thermal conductivity of the liquid crystal epoxy resin composite material prepared by using the liquid crystal epoxy resin monomer of the present invention is 0.434W / (m·K), which is significantly improved compared with the thermal conductivity of 0.188W / (m·K) of ordinary E-51 epoxy resin, and the liquid crystal temperature range is 138°C to 170°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1Infrared spectra of P1 and LCE1 prepared in Example 1;

[0015] Figure 2 is the DSC graph of LCE1 prepared in Example 1;

[0016] Figure 3 XRD pattern of LCE1 prepared in Example 1;

[0017] Figure 4 Polarized light microscope images of LCE1 prepared in Example 1 at 25°C, 140°C, 150°C, 160°C, 170°C, 180°C and 190°C;

[0018] Figure 5 Graph showing thermal conductivity of LCE1 / epoxy resin composite materials with different mass fractions prepared using LCE1 prepared in Example 1 in Example 2;

[0019] Figure 6 The breakdown properties of LCE1 / epoxy resin composite materials with different mass fractions prepared using LCE1 prepared in Example 1 in Example 2;

[0020] Figure 7 : is the volume resistivity of LCE1 / epoxy resin composite materials with different mass fractions prepared in Example 2 using LCE1 prepared in Example 1. DETAILED DESCRIPTION

[0021] Specific implementation method 1: This implementation method is a method for preparing a side chain Schiff base liquid crystal epoxy resin, which is specifically completed by the following steps:

[0022] 1. Preparation of P1:

[0023] ①, 4-biphenyl formaldehyde, p-aminophenol and anhydrous ethanol are mixed to obtain a mixed solution I;

[0024] ②, dissolve p-toluenesulfonic acid in anhydrous ethanol to obtain mixed solution II;

[0025] ③. Add the mixed solution II dropwise to the mixed solution I to obtain a mixed solution III; reflux the mixed solution III for a period of time to obtain a yellow precipitate; wash the yellow precipitate, and then dry it to obtain an intermediate product P1;

[0026] 2. Dissolve the intermediate product P1 and epichlorohydrin in isopropanol, then add tetrabutylammonium bromide, and then heat under reflux for a period of time under stirring and a temperature of 85°C to 95°C, dropwise add a 30% by mass NaOH solution, and continue to stir and react at 85°C to 95°C for a period of time to obtain a reaction product; wash and dry the reaction product to obtain a side chain Schiff base type liquid crystal epoxy resin.

[0027] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the molar ratio of 4-biphenylcarboxaldehyde to p-aminophenol in step 1 is 1:1; the volume ratio of the amount of 4-biphenylcarboxaldehyde to anhydrous ethanol in step 1 is 1 mol:(100 mL to 120 mL). The other steps are the same as those in specific embodiment 1.

[0028] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the mass ratio of p-toluenesulfonic acid to anhydrous ethanol in step 1② is (0.2 g to 0.4 g): 30 mL. The other steps are the same as those of specific embodiments 1 and 2.

[0029] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the molar ratio of the mass of p-toluenesulfonic acid to 4-biphenylcarboxaldehyde in the mixed solution III described in step 1 ③ is (0.2g-0.4g):1mol; the temperature of the reflux reaction described in step 1 ③ is 85°C-95°C, and the reflux reaction time is 6h-8h. The other steps are the same as those of specific embodiments 1 to 3.

[0030] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step 1 ③, anhydrous ethanol is used to wash the yellow precipitate until it is colorless; the drying temperature in step 1 ③ is 40°C to 50°C, and the drying time is 20h to 25h. The other steps are the same as those of specific embodiments 1 to 4.

[0031] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the volume ratio of the amount of the intermediate product P1 described in step 2 to is (0.04 mol to 0.06 mol): (90 mL to 100 mL). The other steps are the same as those of specific embodiments 1 to 5.

[0032] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the volume ratio of epichlorohydrin to isopropyl alcohol in step 2 is (40 mL to 50 mL): (90 mL to 100 mL). The other steps are the same as those of specific embodiments 1 to 6.

[0033] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the volume ratio of the amount of tetrabutylammonium bromide described in step two to isopropanol is (0.45mmol-0.55mmol):(90mL-100mL); the volume ratio of the 30% mass fraction NaOH solution described in step two to isopropanol is (3.33mL-3.70mL):(90mL-100mL). The other steps are the same as specific embodiments one to seven.

[0034] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the heating reflux time in step 2 is 2h to 4h; the stirring reaction time at 85°C to 95°C in step 2 is 1.5h to 3h. The other steps are the same as those in specific embodiments 1 to 8.

[0035] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: in step 2, the reaction product is washed 3 to 5 times with distilled water; the drying temperature in step 2 is 60°C to 80°C, and the drying time is 30h to 35h. The other steps are the same as those in specific embodiments 1 to 9.

[0036] The following examples are used to verify the beneficial effects of the present invention:

[0037] Example 1: A method for preparing a side chain Schiff base type liquid crystal epoxy resin is specifically completed according to the following steps:

[0038] 1. Preparation of P1:

[0039] ①, mix 1 mol of 4-biphenyl formaldehyde, 1 mol of p-aminophenol and 100 mL of anhydrous ethanol to obtain a mixed solution I;

[0040] ②, dissolve 0.3g p-toluenesulfonic acid in 30mL anhydrous ethanol to obtain mixed solution II;

[0041] ③. Add the mixed solution II dropwise to the mixed solution I to obtain a mixed solution III; reflux the mixed solution III at 90°C for 6 hours to obtain a yellow precipitate; wash the yellow precipitate with anhydrous ethanol until the filtrate is colorless, and then dry at 40°C for 24 hours to obtain an intermediate product P1;

[0042] 2. Dissolve 0.05 mol of the intermediate product P1 and 45 mL of epichlorohydrin in 90 mL of isopropanol, then add 0.5 mmol of tetrabutylammonium bromide, heat under reflux for 3 h under stirring conditions and a temperature of 85 ° C, then drop 3.33 mL of a 30% NaOH solution, continue to stir and react at 85 ° C for 2 h to obtain a reaction product; wash the reaction product with distilled water 5 times, and then dry it at 80 ° C for 30 h to obtain a side chain Schiff base liquid crystal epoxy resin (LCE1).

[0043] The chemical reaction formula in step 1 of Example 1 is as follows:

[0044]

[0045] The chemical reaction formula in step 2 of Example 1 is as follows:

[0046]

[0047] Figure 1 Infrared spectra of P1 and LCE1 prepared in Example 1;

[0048] from Figure 1 It can be seen that the intermediate products P1 and LCE1 are at 1612cm -1 There is a characteristic absorption peak of C=N double bond, 3442cm -1 After the intermediate product P1 reacts with epichlorohydrin, the liquid crystal epoxy resin monomer retains the characteristic peak of the C=N double bond and also has an absorption peak at 1029cm -1 A new stretching vibration peak is generated at 750-840 cm-1, corresponding to the COC bond in the liquid crystal epoxy resin monomer. -1 There is an epoxy group absorption peak at , which is preliminarily determined to be the target product.

[0049] Figure 2 is the DSC graph of LCE1 prepared in Example 1;

[0050] from Figure 2 It can be seen that the liquid crystal epoxy resin monomer LCE1 has two endothermic peaks, and the turning point from the crystalline state to the liquid crystal state occurs at 138°C. At this time, the phase state of the liquid crystal epoxy resin begins to change from the crystalline state to the anisotropic liquid crystal state. When the temperature is 170°C, the phase state of LCE1 begins to change from the liquid crystal state to the isotropic liquid state, indicating that the liquid crystal temperature range of the liquid crystal epoxy resin is 138°C to 170°C. LCE1 belongs to the liquid crystal epoxy resin and has liquid crystal properties within the liquid crystal temperature range.

[0051] Figure 3 XRD pattern of LCE1 prepared in Example 1;

[0052] from Figure 3 It can be seen that the characteristic diffraction peak angle (2θ) of smectic liquid crystal epoxy resin is between 2 and 10°, while the characteristic diffraction peak angle (2θ) of nematic liquid crystal is greater than 10°. Figure 2 As shown, the liquid crystal epoxy resin monomer LCE1 has multiple diffraction peaks near 20°, which preliminarily determines that the liquid crystal epoxy resin monomer belongs to a nematic phase structure.

[0053] Figure 4 Polarized light microscope images of LCE1 prepared in Example 1 at 25°C, 140°C, 150°C, 160°C, 170°C, 180°C and 190°C;

[0054] from Figure 4It can be seen that: at 25°C, it can be observed that the liquid crystal epoxy resin monomer is a crystalline substance, and the field of view under the polarizing microscope is relatively dark at this time; with the increase of temperature, the crystalline substance begins to change, and at 138°C the substance begins to melt, the field of view suddenly becomes bright, a liquid crystal phase appears, and colorful rod-shaped liquid crystals can be observed. When the temperature continues to rise, the field of view becomes brighter, the sample is completely transformed into a liquid crystal phase, and birefringence occurs. When the temperature reaches 180°C, the field of view begins to darken, and the birefringence phenomenon begins to disappear. At 190°C, the liquid crystal phase completely disappears, the sample is completely transformed into a liquid, and no substance can be observed under a polarizing microscope; this indicates that the liquid crystal epoxy resin monomer definitely has nematic liquid crystals, and the temperature range is between 138 and 170°C, with obvious liquid crystal characteristics.

[0055] Example 2: LCE1 / epoxy resin composite materials with different mass fractions were prepared using LCE1 prepared in Example 1, specifically by the following steps:

[0056] The curing process is as follows: first, LCE1 and epoxy resin E-51 prepared in Example 1 are added to a 250 mL beaker, a magnetic stirring device is connected, a magnetic stirring bar is placed, the temperature is raised to 190° C. for magnetic stirring, and the mixture in the beaker is observed to be clear and transparent. Stop stirring, and quickly put it into an 80° C. water bath, and at the same time, the water bath is connected to a mechanical stirring device. After stirring for 0.5 h, the curing agent methyl hexahydrophthalic anhydride is added, and stirring is continued for 2 h. The accelerator DMP-30 is added and stirred for 0.5 h. The beaker is then placed in an 80° C. vacuum drying oven to remove bubbles generated during mechanical stirring. After observing that no bubbles are generated in the beaker, the beaker is taken out, and finally the mixture in the beaker is poured into a mold and placed in a 160° C. flat plate vulcanizer, the pressure of the flat plate vulcanizer is set to 10 MPa, and cured for 2 h. The mold is taken out and cooled to room temperature to obtain an LCE1 / epoxy resin composite material.

[0057] The amounts of LCE1, epoxy resin E51, curing agent methyl hexahydrophthalic anhydride and accelerator DMP-30 used in Example 2 are shown in Table 1;

[0058] Table 1

[0059]

[0060] The mass fraction of liquid crystal epoxy resin monomer is obtained according to formula (1):

[0061]

[0062] Figure 5 Graph showing thermal conductivity of LCE1 / epoxy resin composite materials with different mass fractions prepared using LCE1 prepared in Example 1 in Example 2;

[0063] from Figure 5It can be seen that the thermal conductivity of the side chain Schiff base liquid crystal epoxy resin (LCE1) when the mass percentage is 5% is 0.231 W / (m·K), which is 0.043 W / (m·K) higher than that of bisphenol A type E-51 epoxy resin at 0.188 W / (m·K). The thermal conductivity is more significantly improved when the mass percentage of the side chain Schiff base liquid crystal epoxy resin (LCE1) is higher. The thermal conductivity of the side chain Schiff base liquid crystal epoxy resin (LCE1) when the mass percentage is 10%, 20% and 30% is 0.272, 0.356 and 0.434 W / (m·K), respectively, which is 0.084, 0.168 and 0.246 W / (m·K) higher than that of bisphenol A type E-51 epoxy resin at 0.188 W / (m·K). This is mainly due to the presence of Schiff base mesogens in the molecular structure of liquid crystal epoxy resin monomers, which form a tight cross-linked network structure during the curing process with E-51 epoxy resin, while retaining the regularly arranged lattice and the liquid crystal domains unique to liquid crystals, constructing a phonon heat conduction pathway, reducing phonon scattering, lowering thermal resistance, and increasing the thermal conductivity of the composite material; as the content of liquid crystal epoxy resin monomer increases, the range of the liquid crystal domain also increases, further improving the orderliness and tightness of the cross-linked network structure, so the thermal conductivity of the composite material increases with the increase of liquid crystal content.

[0064] Figure 6 The breakdown properties of LCE1 / epoxy resin composite materials with different mass fractions prepared using LCE1 prepared in Example 1 in Example 2;

[0065] from Figure 6 It can be seen that as the content of liquid crystal epoxy resin in LCE1 / epoxy resin composite material increases, its breakdown field strength increases. When the mass fraction is 30wt%, the AC breakdown field strength of the composite material is the highest, and the breakdown field strength of pure epoxy resin is 65.46kV / mm, which is 24.88kV / mm higher than that of pure epoxy resin. Since liquid crystal epoxy resin has good compatibility in E-51 epoxy resin matrix, it can form an ordered cross-linked network structure during curing, improve the defects of E-51 itself, increase the compactness of the internal structure of the composite material, reduce the average free path of the molecules inside the composite material, and make it more difficult to form a conductive path. Therefore, the breakdown field strength of LCE1 / epoxy resin composite material increases with the increase of liquid crystal epoxy resin content.

[0066] Figure 7 is the volume resistivity of LCE1 / epoxy resin composite materials with different mass fractions prepared using LCE1 prepared in Example 1 in Example 2;

[0067] from Figure 7It can be seen that the higher the volume resistivity, the better the insulation performance of the material. The volume resistivity of the insulating material is mainly affected by the carrier mobility and the carrier concentration. The maximum volume resistivity of the composite material appears when the mass fraction of the side chain Schiff base liquid crystal epoxy resin (LCE1) monomer is 30wt%; the volume resistivity of the composite material varies within the same order of magnitude with a small amplitude. Since the side chain Schiff base liquid crystal epoxy resin (LCE1) monomer has good compatibility with the E-51 epoxy resin and forms a cross-linked network structure, it will make up for the defects of the material, increase the intermolecular force, and reduce the free volume of the molecule, resulting in a decrease in the carrier concentration and the carrier mobility, thereby increasing the volume resistivity of the LCE1 / epoxy resin composite material.

Claims

1. A method for preparing a side chain Schiff base type liquid crystal epoxy resin, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of P1: ①, 4-biphenyl formaldehyde, p-aminophenol and anhydrous ethanol are mixed to obtain a mixed solution I; ②, dissolve p-toluenesulfonic acid in anhydrous ethanol to obtain mixed solution II; ③. Add the mixed solution II dropwise to the mixed solution I to obtain a mixed solution III; reflux the mixed solution III for a period of time to obtain a yellow precipitate; wash the yellow precipitate, and then dry it to obtain an intermediate product P1; 2. Dissolve the intermediate product P1 and epichlorohydrin in isopropanol, then add tetrabutylammonium bromide, and then heat under reflux for a period of time under stirring and a temperature of 85°C to 95°C, dropwise add a 30% by mass NaOH solution, and continue to stir and react at 85°C to 95°C for a period of time to obtain a reaction product; wash and dry the reaction product to obtain a side chain Schiff base type liquid crystal epoxy resin.

2. The method for preparing a side chain Schiff base type liquid crystal epoxy resin according to claim 1, characterized in that The molar ratio of 4-biphenylcarboxaldehyde to p-aminophenol in step 1 is 1:1; the volume ratio of the amount of 4-biphenylcarboxaldehyde to anhydrous ethanol in step 1 is 1 mol:(100 mL to 120 mL).

3. The method for preparing a side chain Schiff base type liquid crystal epoxy resin according to claim 1, characterized in that The mass ratio of p-toluenesulfonic acid described in step 1② to anhydrous ethanol is (0.2g~0.4g):30mL.

4. The method for preparing a side chain Schiff base type liquid crystal epoxy resin according to claim 1, characterized in that The molar ratio of the mass of p-toluenesulfonic acid to 4-biphenylaldehyde in the mixed solution III described in step 1③ is (0.2g~0.4g):1mol; the temperature of the reflux reaction described in step 1③ is 85℃~95℃, and the reflux reaction time is 6h~8h.

5. The method for preparing a side chain Schiff base type liquid crystal epoxy resin according to claim 1, characterized in that In step 1③, anhydrous ethanol is used to wash the yellow precipitate until it is colorless; the drying temperature in step 1③ is 40℃~50℃, and the drying time is 20h~25h.

6. The method for preparing a side chain Schiff base type liquid crystal epoxy resin according to claim 1, characterized in that The volume ratio of the amount of the intermediate product P1 described in step 2 to isopropanol is (0.04 mol to 0.06 mol): (90 mL to 100 mL).

7. The method for preparing a side chain Schiff base type liquid crystal epoxy resin according to claim 1, characterized in that The volume ratio of epichlorohydrin to isopropyl alcohol described in step 2 is (40mL-50mL):(90mL-100mL).

8. The method for preparing a side chain Schiff base type liquid crystal epoxy resin according to claim 1, characterized in that The volume ratio of the amount of tetrabutylammonium bromide described in step 2 to isopropanol is (0.45mmol-0.55mmol):(90mL-100mL); the volume ratio of the 30% NaOH solution described in step 2 to isopropanol is (3.33mL-3.70mL):(90mL-100mL).

9. The method for preparing a side chain Schiff base type liquid crystal epoxy resin according to claim 1, characterized in that The heating reflux time in step 2 is 2h to 4h; the stirring reaction time at 85°C to 95°C in step 2 is 1.5h to 3h.

10. The method for preparing a side chain Schiff base type liquid crystal epoxy resin according to claim 1, characterized in that In step 2, the reaction product is washed 3 to 5 times with distilled water; the drying temperature in step 2 is 60° C. to 80° C., and the drying time is 30 h to 35 h.